2019
DOI: 10.1097/jps.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Improving Pediatric Patient Readiness for Gastrostomy Placement via Caregiver's Preconsult Involvement

Abstract: Introduction Patients and families referred for gastrostomy tube placement were rarely informed or prepared for the presurgical evaluations required to schedule surgery. These requirements are embedded in a Gastrostomy Readiness Checklist (GRC) that must be completed before scheduling surgery. The GRC was intended to be initiated by the referring provider, yet this was rarely done. As a result, registered nurses (RNs) assumed responsibility for the GRC. Families were often dissatisfied with the nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…For surgical patients, NPs are frequently utilized for preoperative education and may be better than physicians at addressing the psychosocial aspects of preparing for surgery (Frisch, Johnson, Timmons, & Weatherford, 2010). A recent study at Seattle Children's Hospital found that an Registered Nurse-driven protocol to assist parents in completing a preoperative safety checklist before scheduling G-tube placement increased readiness for surgery and reduced the number of clinic visits needed before scheduling surgery (Albin & McCormick, 2019). In G-tube patients, a nursing-run preoperative educational session may reduce postoperative ED visits (Barry et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For surgical patients, NPs are frequently utilized for preoperative education and may be better than physicians at addressing the psychosocial aspects of preparing for surgery (Frisch, Johnson, Timmons, & Weatherford, 2010). A recent study at Seattle Children's Hospital found that an Registered Nurse-driven protocol to assist parents in completing a preoperative safety checklist before scheduling G-tube placement increased readiness for surgery and reduced the number of clinic visits needed before scheduling surgery (Albin & McCormick, 2019). In G-tube patients, a nursing-run preoperative educational session may reduce postoperative ED visits (Barry et al, 2018).…”
Section: Introductionmentioning
confidence: 99%